Influência de diferentes agregados miúdos reciclados nas propriedades de microconcretos com relação água/cimento e trabalhabilidade estabelecidas com auxílio de aditivo superplastificante - Gilberto Alves da Silva Neto (2019)
The large amount of construction and demolition waste (CDW), coupled with the fact that construction is the largest consumer of non-renewable natural resources, has negatively affected the environment. Therefore, a possible solution is to recycle the CDW. However, some characteristics of the recycled aggregates (RAs) may harm the properties of the cementitious composites in the fresh and hardened states. Thus, the combination of the effects of RAs and water reducing admixture is seen as favorable for the production of recycled cementitious composites. The aim of this work is to evaluate the influence of the type of construction waste (ceramic, mortar or concrete) used as partial replacement of the fine natural aggregate (FNA) for a condition of constant workability, obtained with the aid of superplasticizer additive. Microconcretes were casting using the Brazilian Portland cement CP VARI, polycarboxylates-based superplasticizer, and partial replacement of FNA by different fine recycled aggregates (FRAs). The w/c ratio and the superplasticizer content were varied for each type of FRA, considering the limit consistency of 250±15 mm. The mechanical behavior (axial compression strength and dynamic modulus of elasticity) and durability (water absorption by immersion and by capillarity, and electrical-volumetric resistivity) of microconcretes were evaluated. The physical characteristics of the FRAs were diverse, but in general, a continuous particle-size distribution curve was obtained, promoting a better packaging of the constituents in the microconcrete mixture. Together with the reduction of the effective w/c ratio in the paste, due to the higher water absorption of RAs, the microconcretes showed out an increased compressive strength and a reduced water absorption. Consequently, there was an increase in the electrical resistivity of microconcretes for the combination of FNA and FRAs. In relation to the effect of the superplasticizer in the mixtures, in general, it did not alter or improved the evaluated microconcretes properties.